A dynamic theory of multiple borrowing - Green, Daniel; Liu, Ernest (Journal of Financial Economics, 2021)
Multiple borrowing—when borrower obtains overlapping loans from multiple lenders—is a common phenomenon in many credit markets. We build a tractable, dynamic model of multiple borrowing and show that, because overlapping creditors can impose default externalities on each other, expanding financial access by introducing more lenders can backfire. Capital allocation is distorted away from the most productive uses. Entrepreneurs choose inefficient endeavors with low returns to scale. These problems are exacerbated when investments become more pledgeable or when borrowers have access to more lenders, explaining why increased access to finance does not always improve outcomes.